PROBABILITY OF THE UTILITY NETWORKS DOUBLE-RING STRUCTURES’ CONNECTIVITY FOR SITES WITH VARIOUS RELIABILITY - Usenko, V. H.; Kodak, О. А. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The analytical description study results on probability of connectivity for the structures used to model the reliability of various complicated systems are presented. Expressions are formed to calculate the connectivity probability of systems that have structural redundancy. The characteristic components of the formulas are distinguished and they are systematized according to their increasing complexity and the number of elements. The features of the equations’ structure permitting to conveniently formulate the probability of the structures connectivity in the process of their construction and transformations are determined. The examples show the formation of formulas and their structural parts at various levels of complexity. The use of the ratio value of the network structure element’s unreliability and its reliability is justified, thus reducing the awkwardness of exact expressions for the connectivity probability of network structures and substantially improves the compactness and convenience of using the equations.
Keywords: structural modeling; connectivity probability; reliability of a system with different reliability of elements